2010
DOI: 10.1002/adem.201000109
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Properties of a Printed Sol–Gel Matrix Composite

Abstract: Low temperature processable materials with high dielectric constants are required for application on flexible organic substrates, for example, in printed electronics. To date, mainly organic polymers with embedded functional particles have been investigated for this purpose. For the first time, we present a printable dielectric composite material composed of ferroelectric high permittivity particles (BaTiO3) bonded by a mainly inorganic sol–gel derived network. The exemplary optimization of the properties by v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Moreover and in order to reduce leakage currents of thin dielectric films, the use of cross-linked polymer blend (CPB), fabricated both by spin coating and gravure printing, has been proposed. 103 Lehnert et al 104 reported a printable high dielectric constant material composed of ferroelectric barium titanate (BaTiO 3 ) particles. A hybrid ink consisting of BaTiO 3 and PMMA has also been employed as a gate insulator in fully printed TFTs fabricated on a flexible PET substrate.…”
Section: Insulating Dielectricsmentioning
confidence: 99%
“…Moreover and in order to reduce leakage currents of thin dielectric films, the use of cross-linked polymer blend (CPB), fabricated both by spin coating and gravure printing, has been proposed. 103 Lehnert et al 104 reported a printable high dielectric constant material composed of ferroelectric barium titanate (BaTiO 3 ) particles. A hybrid ink consisting of BaTiO 3 and PMMA has also been employed as a gate insulator in fully printed TFTs fabricated on a flexible PET substrate.…”
Section: Insulating Dielectricsmentioning
confidence: 99%
“…In order to increase the k value of the dielectric it is common to add high-k materials such as barium titanate (BaTiO 3 ). This approach has been often reported in the literature [6,11,12,13], with k values of printed dielectrics reported as high as 102 [13]. However the approach has limitations [14], chiefly of which is the difficulty in obtaining a thin, defect free film with a suitable nanoparticle loading.…”
Section: Introductionmentioning
confidence: 99%
“…When printing on flexible substrates, ceramic/polymer composites can be used as a dielectric material. These composites have a good manufacturability and can have relatively high permittivities without the need for further thermal treatment [ 8 , 9 , 10 , 11 , 12 ]. For the application under ambient conditions, a temperature-independent permittivity is an important prerequisite.…”
Section: Introductionmentioning
confidence: 99%